Improving the Communication and Credibility of Government Media in Response to Public Health Emergencies: Analysis of Tweets From the WeChat Official Accounts of 10 Chinese Health Commissioners - Li, Zhigang; Wang, Manjia; Zhong, Jialong; Ren, Yiling (Frontiers in Public Health, 2022)
Background: A significant public health emergency has appeared worldwide since the beginning of 2020. The spread of negative information about COVID-19 on social media poses a challenge and threat to public health disposition and the credibility of government public opinion. Objective: Analyze the rules and characteristics of government media in disseminating information on public emergencies, and study ways and means to improve the information dissemination power and credibility of the government public. Method: Taking 10 Chinese government media WeChat public websites as examples, based on relevant theories and measures of information econometrics, used Python crawler tool to collect data of 10 WeChat general numbers related tweets. In addition, various devices such as ROST, Ucinet, and SPSS were used for statistical analysis and co-word analysis of the data. Result: A total of 6,612 tweets were collected. The tweets were divided into six types: epidemic overview release, epidemic prevention and control measures, scientific disinformation, epidemic line assistance stories, epidemic impact, and negative impact. The number and content of tweets were consistent with the development of this public health emergency, with 8 a.m. being the time when the most information was disseminated to the public. General numbers with low coupling and a high number of tweets have a higher reading rate of 10,000+ and a higher average of the number in view and gain higher public recognition. Conclusion: The articles pushed by government media WeChat public numbers are valuable, exciting, and touching, and their communication power is more robust. Second, the credibility of government media WeChat's general numbers with a high degree of independent innovation and activity is more elevated. Government media can improve the governance of public opinion on public health emergencies by enhancing their communication power and credibility.